Hubungan Paritas Ibu Bersalin dengan Kejadian Perpanjangan Kala 1 Fase Aktif - Layla Imroatu Zulaikha; Dian Permatasari (SAKTI BIDADARI (Satuan Bakti Bidan Untuk Negeri), 2022)
The maternal mortality rate is mostly caused by prolonged labor as much as 8%, one of which is caused by the extension of the first stage of the active phase. 16.7% maternity mothers experienced an extension of the first stage of the active phase caused by parity factors. The purpose of this study was to determine the relationship between maternal parity and the incidence of prolongation of the active phase.This research design is correlation analytic, based on cross sectional time. The population and sample of this study were all mothers who gave birth in January-May 2022 as many as 35 respondents using saturated sampling technique. The independent variable is maternal parity, while the dependent variable is the incidence of prolongation of the first stage of the active phase. Data obtained using partograph with contingency coefficient statistical test.The results of statistical tests obtained X2count (7.047) > X2table (5.991) with a contingency coefficient of 0.409 so it can be concluded that there is a moderate relationship between maternal parity and the extension of stage 1 of the active phase.For mothers with primiparas, it is expected to routinely carry out antenatal checks so that high risks are detected early during delivery, multiparous mothers minimize the occurrence of extension of the active phase 1 by following the advice of midwives during labor and grandemultipara mothers are advised not to have more children so that there is no risk high rates of pregnancy and childbirth with participation in family planning programs